2020
DOI: 10.25046/aj050450
|View full text |Cite
|
Sign up to set email alerts
|

A Framework of E-Procurement Technology for Sustainable Procurement in ISO 14001 Certified Firms in Malaysia

Abstract: With the current emerging development pattern in Malaysia, E-Government has been unveiled by the Malaysian Government to be one of the multimedia super corridor flagship applications to implement digital technology to improve government operations. Eprocurement was originally utilized by businesses to minimize turnaround times and prices, but recently it was often used as a platform for sustainable procurement. However, there have been few attempts to investigate E-procurement technology in Malaysia concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
(90 reference statements)
0
7
0
1
Order By: Relevance
“…Permasalahan yang terakhir adalah pendekatan yang protektif, artinya banyaknya pembatasan dalam keikut sertaan dunia usaha seperti penggolongan usaha (besar, menengah dan kecil) dalam kegiatan pengadaan barang. Pendekatan ini tidak mendapatkan sumbangan yang berarti bagi peningkatan daya saing nasional dan tumbuh kembangnya usaha (Irawan, 2020) E-Procurement adalah sebuah sistem lelang dalam pengadaan barang dan jasa dengan memanfaatkan teknologi informasi dan komunikasi bebasis internet (Singh et al, 2020). Dengan E-Procurement proses lelang dapat berlangsung secara efektif, efisien, terbuka, bersaing, transparan, adil/tidak diskriminatif dan akuntabel sehingga diharapkan dapat mencerminkan keterbukaan/transparansi dan juga meminimalisir praktik curang KKN (Korupsi, Kolusi dan Nepotisme) dalam lelang pengadaan barang yang dapat merugikan keuangan negara (Chen et al, 2022).…”
Section: Pendahuluanunclassified
“…Permasalahan yang terakhir adalah pendekatan yang protektif, artinya banyaknya pembatasan dalam keikut sertaan dunia usaha seperti penggolongan usaha (besar, menengah dan kecil) dalam kegiatan pengadaan barang. Pendekatan ini tidak mendapatkan sumbangan yang berarti bagi peningkatan daya saing nasional dan tumbuh kembangnya usaha (Irawan, 2020) E-Procurement adalah sebuah sistem lelang dalam pengadaan barang dan jasa dengan memanfaatkan teknologi informasi dan komunikasi bebasis internet (Singh et al, 2020). Dengan E-Procurement proses lelang dapat berlangsung secara efektif, efisien, terbuka, bersaing, transparan, adil/tidak diskriminatif dan akuntabel sehingga diharapkan dapat mencerminkan keterbukaan/transparansi dan juga meminimalisir praktik curang KKN (Korupsi, Kolusi dan Nepotisme) dalam lelang pengadaan barang yang dapat merugikan keuangan negara (Chen et al, 2022).…”
Section: Pendahuluanunclassified
“…Moreover, the TAM predicts the motivation to execute a variety of abilities by assuring that organizations function smoothly and efficiently. The key components of the TAM, which can accurately evaluate the individual's attitude and intent regarding EPT acceptance and actual use in procurement processes, are PEOU and PU [61]. This theory shows that the recognition and usage of technology depend on the users' feelings and perceived advantages of the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To combat the immobility that frequently characterizes SPP, governments and other key stakeholders have been using a range of legal and policy tools to adopt and integrate SPP and their associated practices in diverse organizations throughout the world [101]. As identified in the relevant literature, the twelve dimensions of sustainable procurement practices include environmental considerations; diversity in suppliers; safety; human rights; philanthropy or charity work; purchasing from small and local enterprises; a commitment to strong leadership; policy and regulatory requirements; stringent tender terms and evaluation; management and monitoring of progress; competitive edge and technical competence [33,43,61,102]. Some of the activities covered in life-cycle assessments are the designing of goods; supplier demands such as recycling, reducing waste, and reuse; the procurement of lighterweight packaging; and the acquisition of reusable packaging.…”
Section: Green Procurement Practices (Gpp)mentioning
confidence: 99%
See 1 more Smart Citation
“…The research results found in Malaysia stated that the Implementation of e-procurement had yet to find a definite and reliable technical pattern. The eprocurement system is stated to be not optimal and cannot guarantee the sustainability of the procurement system in a sustainable manner (Singh et al, 2020). Implementation of systems that can be used in e-government must have sustainability for the Implementation of systems that are integrated (Habibullah, 2010).…”
Section: Introductionmentioning
confidence: 99%